Investigating co-presence and collaboration dynamics in realtime virtual reality user interactions - Yousefdeh, Seyed Alireza Ghasempour; Oyelere, Solomon Sunday (Frontiers in Virtual Reality, 2024)
As Virtual Reality (VR) technologies advance and gain popularity, their potential as powerful tools for collaboration is increasingly recognized. VR facilitates interaction with the virtual presence of individuals who are not physically co-located. Understanding the dynamics of user interactions and the cognitive perception of virtual presence quality is essential for this technology's progression. This paper introduces CoCoVR, a VR measurement method for measuring the sense of co-presence and collaboration quality among users through real-time data collection and analysis. CoCoVR is evaluated across various scenarios to understand user interactions in VR under different conditions. An extensive analysis of recent literature has been performed that identified avatar realism and communication as two key factors influencing co-presence and collaboration. The experiment includes a custom VR application, the Soma cube puzzle, and real-time sensors. A between-subject experiment was conducted to collect and analyzes real-time data on collaboration and co-presence. This study integrates both objective and subjective measures, offering deeper insights into the immersive experience and its impact on collaborative tasks. The findings show that avatar realism enhances the feeling of co-presence and that communication methods substantially improve collaboration. Additionally, the study found that measuring physiological responses can serve as a novel method for evaluating the quality of user collaborations.CCS Concepts: • Human-centered computing → Empirical studies in collaborative and social computing.